TINGKAT KEMAMPUAN SOFT SKILLS FUNGSIONARIS LEMBAGA KEMAHASISWAAN FAKULTAS ILMU KEOLAHRAGAAN UNIVERSITAS NEGERI SEMARANG ANGKATAN 2009 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the level of soft skills functionaries Student Organizations Faculty of Sport Science , State University of Semarang 2009.Sampling in this study used purposive sampling technique that uses a sample of 83 students who take the class of 2009 student organizations . The author uses descriptive quantitative research methods with the method of the survey , and collection of information or data using questionnaires , the study took a sample of the population and the use of questionnaires as a data collection tool.Based on the results of data processing , obtained the soft skills that students can be described as follows : for 36 students ( 43.37 % ) in the high category , by 47 students ( 56.63 % ) in the medium category , for 0 students ( 0 % ) in low category Referring to the results of the study concluded that the level functionaries Soft Skills Student Organizations School of Sport Science , State University of Semarang Force 2009 in the category of being.